Optimization study of syngas production from catalytic air gasification of rice husk - Loy, A.C.M. (Alpha Publishers, 2020)
In this analysis, catalytic air gasification of the rice husk was investigated to optimise the composition of hydrogen and syngas using a thermogravimetric analyser coupled with a mass spectrometer. The fixed bed reactor is then used as a pilot plant to determine the practicality of the optimal parameters obtained for upscaling from the thermogravimetric analyzer test. The catalyst used is coal bottom ash chosen and obtained from a nearby power plant based on a previous analysis. The findings from the thermogravimetric analyser test showed that at reaction temperature of 900oC, rice husk particle size of 250 Âµm, catalyst quantities of 10, and air to biomass ratio of 1.25 were the optimum input parameters for syngas formulation to obtain product gas with 73.8 of syngas composition. 76.2 of the composition of syngas is derived from a fixed bed reactor, 3.25 more than the previous test. In addition, 84.1 of the gaseous substance yield, including syngas and CH4, was obtained using the coal bottom ash catalyst in catalytic air gasification. This demonstrated the promise of coal bottom ash in catalytic gasification as a replacement for industrial catalysts. Finally, to determine the effect of temperature, particle size, air to biomass ratio, and coal bottom ash loading on the production of H2 and syngas, the main component analysis was applied. Production of H2 tends to be extremely sensitive to the temperature of the reaction. Meanwhile, there was a positive association between particle size, air to biomass ratio and catalyst loading with CO2 and CH4, but a negative correlation with H2. Â© 2020 Alpha Publishers.